2006
DOI: 10.1589/jpts.18.33
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocyte Growth Factor in Mouse Soleus Muscle Increases with Reloading after Unloading

Abstract: Abstract. Hepatocyte growth factor (HGF) has been suggested as a mitogen for skeletal muscle satellite cells and participates in skeletal muscle hypertrophy. The present study assessed HGF levels in mouse soleus and plantaris muscles during 14 days of tail suspension and 3 days of reloading using the enzymelinked immunosorbent assay. Immunohistochemical analyses were used to determine the locations of HGF, its receptor (c-Met) and proliferating cell nuclear antigen. In normal mice, HGF contents were 4.4 ± 0.5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 52 publications
1
10
1
Order By: Relevance
“…In this study, HGF levels were 3.4-6.2 ng in the gastrocnemius muscle at 4-24 weeks of age. These data are comparable with data from recent study 17) . HGF protein levels in rat skeletal muscles were detected until 24 weeks old.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In this study, HGF levels were 3.4-6.2 ng in the gastrocnemius muscle at 4-24 weeks of age. These data are comparable with data from recent study 17) . HGF protein levels in rat skeletal muscles were detected until 24 weeks old.…”
Section: Discussionsupporting
confidence: 92%
“…HGF protein levels in rat skeletal muscles were detected until 24 weeks old. HGF promotes the proliferation of adult myoblasts 18) and is present in adult tibialis anterior 13) , soleus and plantaris muscles 17) . However, according to northern blot analysis, HGF mRNA signals could be detected until 10 days after birth, but could not be detected in adult skeletal muscle 19) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…; Tanaka et al . ) and that their major sources may be activated, including proliferating satellite cells (Alterio et al . ; Lafyatis et al .…”
Section: Discussionmentioning
confidence: 99%
“…Although the precise mechanism of satellite cell activation induced by hepatocyte growth factor (HGF) is unclear, it is one of the key events in this recovery process 1 , 2 , 3 , 4 , 5 ) . In fact, previous studies using experimental animal models have demonstrated that satellite cell activation and HGF production are induced by activities that cause continuous muscle contraction, such as high-intensity running for 30 min, synergist muscle ablation, contralateral continuous overloading by ablation of a sciatic nerve, and reloading 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ) . However, in clinical physical therapy, it is difficult to perform high-intensity exercise for 30 min or longer.…”
Section: Introductionmentioning
confidence: 99%